(untitled) (CAHIERS MAGELLANES-NS, 2024)
The organisation faces a difficult problem with employee retention. The focus of this study was employee retention tactics. The organization's greatest asset is its workforce. Management needs to pay attention to employee happiness if they want to keep talented and dedicated staff members in the company. Determine the causes of employee attrition and take steps to address them. The goal of this study is to demonstrate the importance of staff retention in the modern workplace and the potential consequences for both the organisation and the industry if organisations fail to recognise this need and take prompt action.